PRAKTEK PARANORMAL DALAM KAJIAN HUKUM PIDANA DI INDONESIA - Arthani, Ni Luh Gede Yogi (Jurnal Advokasi, 2015)
Beliefs about the supernatural powers are a culture of the community. Belief in supernatural powers has led many paranormal practices. In this study will be discussed two issues those criminalization supernatural deeds in criminal law and public belief system of supernatural powers. Oracle can have both positive and negative connotations. Negative behavior of the oracle is known as witchcraft (âsantetâ). The criminalization of witchcraft in the draft Penal Code is still debated. Provisions concerning the mystical act have stipulatedÂ in Article 545, 546, and 547 of the Criminal Code. Belief in a supernatural power is not separated from the culture of the community who believe in the power of an object, âreligiomagisâ nature in customary law and the belief in the existence of spirits in the scriptures.